2015
DOI: 10.1371/journal.pone.0120386
|View full text |Cite|
|
Sign up to set email alerts
|

Functional Analysis of Free Fatty Acid Receptor GPR120 in Human Eosinophils: Implications in Metabolic Homeostasis

Abstract: Recent evidence has shown that eosinophils play an important role in metabolic homeostasis through Th2 cytokine production. GPR120 (FFA4) is a G protein-coupled receptor (GPCR) for long-chain fatty acids that functions as a regulator of physiological energy metabolism. In the present study, we aimed to investigate whether human eosinophils express GPR120 and, if present, whether it possesses a functional capacity on eosinophils. Eosinophils isolated from peripheral venous blood expressed GPR120 at both the mRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 36 publications
(58 reference statements)
2
24
0
Order By: Relevance
“…The stimulation of eosinophils with a synthetic GPR120 agonist led to the increased expression of IL‐4 and the inhibition of apoptosis. These findings suggest that eosinophils might function as nutrient sensors . Finally, there is a strong link between eosinophils and the arachidonic acid metabolism.…”
Section: Tissue Ligands Regulatory For Eosinophil Accumulation Phenomentioning
confidence: 86%
See 3 more Smart Citations
“…The stimulation of eosinophils with a synthetic GPR120 agonist led to the increased expression of IL‐4 and the inhibition of apoptosis. These findings suggest that eosinophils might function as nutrient sensors . Finally, there is a strong link between eosinophils and the arachidonic acid metabolism.…”
Section: Tissue Ligands Regulatory For Eosinophil Accumulation Phenomentioning
confidence: 86%
“…Human eosinophils also express retinoic acid receptors (RARs); retinoic acids are potent inhibitors of human eosinophil apoptosis and upregulate eosinophil expression of CCR3 . Moreover, human eosinophils have been shown to express multiple prostaglandin receptors and GPR120, a G protein‐coupled receptor for long‐chain fatty acids . The stimulation of eosinophils with a synthetic GPR120 agonist led to the increased expression of IL‐4 and the inhibition of apoptosis.…”
Section: Tissue Ligands Regulatory For Eosinophil Accumulation Phenomentioning
confidence: 99%
See 2 more Smart Citations
“…To date, most extensively investigated physiological role of GPR120/FFA4 is its positive effect on insulin sensitivity, which has sparked broad interest into the development of GPR120/FFA4 agonists as novel antidiabetics . In recent years, it has been shown that FFA4 is also expressed on immune cells, including monocytes/macrophages, dendritic cells, and eosinophils, suggesting that GPR120/FFA4 may mediate immunomodulatory actions of ω3‐PUFAs. In line with this notion, in vitro activation of GPR120/FFA4 in macrophages curbs their immune response to NLPR3 inflammasome, TLR4, or TNF‐α activation, and in vivo GPR120 is required for ω3‐PUFAs to counteract adipose tissue inflammation induced by high‐fat diet in mice by limiting the recruitment of monocyte/macrophages into adipose and reducing the release of proinflammatory M1 macrophage‐derived immunomediators, such as IL‐1β, TNF‐α, MCP‐1, and IL‐6, while in parallel promoting the expression of antiinflammatory M2 macrophages, such as IL‐10, arginase 1, Ym‐1, and Clec7a .…”
Section: Introductionmentioning
confidence: 99%